ANALISIS HISTORISITAS HADIS PERANGILAH MANUSIA SEHINGGA MENGUCAP LĀ ILĀHA ILLĀLLAH MENURUT PERSPEKTIF HARALD MOTZKI - Muhamad Deden Jalaludin Sayuti; Lukman Zain Muhamad Sakur; Ahmad Faqih Hasyim (IAIN Syekh Nurjati Cirebon, 2021)
This research is motivated by the reliability of the narration of hadith which has become a controversy or debate among Muslim and Western scholars. The study of authenticity is a difficult task. A large number of hadiths and the complicated forms of hadith narration have created a critical and skeptical attitude from hadith scholars, especially from the orientalists. Especially in the hadith “fight people until everyone says lā ilāha illāllah”, the hadith briefly illustrates that Islam is a strict religion. Of course, it will cause polemics when the hadith is not carried out further research. It seems that the right method to see the history of the hadith is the isnad cum matn method used by Harald Motzki. Because Harald Motzki is an orientalist figure who studies hadith a lot about history. The purpose of this study is to describe the research method on the authenticity of a hadith by both Western and Muslim scholars and to describe the method used by Harald Motzki in researching the hadith above. So that the need to find the history of the hadith can be answered. The research design uses a qualitative method based on library research. The results of this study show that Abu Hurairah is a real common link, that is, a person who collects and disseminates hadith to his students. And the hadith is estimated to have begun to be spread by Abi Hurairah in the year 23 H to 57 H in Medina.